2021
DOI: 10.3390/genes12020304
|View full text |Cite
|
Sign up to set email alerts
|

A Deadly Cargo: Gene Repertoire of Cytotoxic Effector Proteins in the Camelidae

Abstract: Cytotoxic T cells and natural killer cells can kill target cells based on their expression and release of perforin, granulysin, and granzymes. Genes encoding these molecules have been only poorly annotated in camelids. Based on bioinformatic analyses of genomic resources, sequences corresponding to perforin, granulysin, and granzymes were identified in genomes of camelids and related ungulate species, and annotation of the corresponding genes was performed. A phylogenetic tree was constructed to study evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
3
2
0
Order By: Relevance
“…For example, the amino acid sequences of mouse and human GZMB are about 70% identical, while the similarities between GZMs of other subfamilies are much lower, even with the same species 2 . We have observed this situation also in camelids 43 and the same differentiation between GZMs subfamilies can be observed for the annotated felid genes.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…For example, the amino acid sequences of mouse and human GZMB are about 70% identical, while the similarities between GZMs of other subfamilies are much lower, even with the same species 2 . We have observed this situation also in camelids 43 and the same differentiation between GZMs subfamilies can be observed for the annotated felid genes.…”
Section: Discussionsupporting
confidence: 82%
“…We have shown previously that camels possess one or two variants for trypsin-like granzymes (GZMA and GZMK), while their chymotrypsin-like granzymes were more diverse with three to five variants of GZMB and two to four variants of GZMH. 43 The low level of polymorphism of GZM genes in Felidae species (Table 3) is similar to the findings in dog genes. Exceptions to this finding include GZMK in Prionailurus bengalensis and Panthera leo with F I G U R E 3 Phylogenetic tree of felid granzyme GZMB based on merged sets of coding sequence haplotypes.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Interestingly, we also found that the marker genes (GNLY, PRF1, GZMB, and NKG7) of CTLs was higher in the long-term group than those in the short-term group, the result has not been reported before. CTLs can kill target cells through the expression and release of perforin and granzymes that are encoded by GNLY, PRF1, and GZMB, 43 and GNLY can induce recruitment and activation of antigen-presenting cells (APCs) and consequently promote the generation of the immune response. 44 NKG7 is a regulator of lymphocyte granule exocytosis and downstream inflammation, 45 suggesting that CTLs activation may contribute PF after long-term PD.…”
Section: Discussionmentioning
confidence: 99%